2′-O methylation of RNA cap in SARS-CoV-2 captured by serial crystallography - Wilamowski, Mateusz (Proc Natl Acad Sci U S A, 2021)
The genome of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) coronavirus has a capping modification at the 5′-untranslated region (UTR) to prevent its degradation by host nucleases. These modifications are performed by the Nsp10/14 and Nsp10/16 heterodimers using S-adenosylmethionine as the methyl donor. Nsp10/16 heterodimer is responsible for the methylation at the ribose 2′-O position of the first nucleotide. To investigate the conformational changes of the complex during 2′-O methyltransferase activity, we used a fixed-target serial synchrotron crystallography method at room temperature. We determined crystal structures of Nsp10/16 with substrates and products that revealed the states before and after methylation, occurring within the crystals during the experiments. Here we report the crystal structure of Nsp10/16 in complex with Cap-1 analog ((m7)GpppA(m2′-O)). Inhibition of Nsp16 activity may reduce viral proliferation, making this protein an attractive drug target.